How can I derive an equation to find the sum of an arithmetic sequence?

This isn't a requirement of many courses but understanding and proving mathematics has order is what makes mathematics unique and enjoyable to many.
Imagine the sum of a sequence with n terms, denoted Sn, which has an initial value, a, and a constant value, d, added on to each term.
For example, my sequence could be:
1, 6, 11, 16... which would make a = 1 and d = 5.
Then Sn = 1 + 6 + 11 + 16 +...
So to be more general,
Sn = + (a+d) + (a+2d) + ...+ (a+(n-2)d) + (a+(n-1)d)
Sn = (a+(n-1)d) + (a+(n-2)d) +...+ (a+2d) + a [reverse Sn]
Add both the sums together: add the first term to the other first term, then the second to the other second and so on.
2Sn = (2a+(n-1)d) + (2a+(n-1)d) +...+ (2a+(n-1)d) + (2a+(n-1)d)
There are n amounts of (2a+(n-1)d), as there are n terms, so this can be factored out.
2Sn = n(2a + (n-1)d)
=> Sn = 0.5n(2a + (n-1)d)    [divide by 2]

Answered by Rhys H. Maths tutor

3894 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Given that y = (3x^4 + x)^5, find dy/dx using the chain rule.


The curve C has equation y = (x^2 -4x - 2)^2. Point P lies on C and has coordinates (3,N). Find: a) the value of N. b) the equation of the tangent to C at the point P, in the form y=mx+c where m and c are constants to be found. c) determine d^2y/dx^2.


What is the best way to prove trig identities?


When integrating, why do we add a constant to the resulting equation?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences